Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

329 = (25)9 = 245 < 252 = (24)13=1613<1813
=> (-32)9 > (-18)13

Ta có : \(A=\left(1-\frac{1}{2}\right)\left(1-\frac{1}{3}\right)...\left(1-\frac{1}{19}\right)\left(1-\frac{1}{20}\right)\)
\(=\frac{1}{2}.\frac{2}{3}....\frac{18}{19}.\frac{19}{20}\)
\(=\frac{1.2....18.19}{2.3...19.20}\)
\(=\frac{1}{20}>\frac{1}{21}\)
Vậy A > 1/21

Ta có :
\(M=\frac{3}{4}.\frac{8}{9}.\frac{15}{16}.....\frac{99}{100}=\frac{3.8.15.....99}{4.9.16.....100}=\frac{1.3.2.4.3.5.....9.11}{2.2.3.3.4.4.....10.10}\)\(=\frac{1.2.3...9}{2.3...10}.\frac{3.4...11}{2.3...10}=\frac{1}{10}.\frac{11}{2}=\frac{11}{20}< \frac{11}{19}\)
ta có M = (1- 1/4) (1- 1/9)... ( 1- 1/100)
= 3/2^2.8/3^2 ... 99/10^2
= 1.3/2^2 . 2.4/3^2 ... 9.11/10^ 2
= 1.2.3...9/ 2.3.4...10 . 3.4.5... 11/ 2.3.4... 10
= 1/10 . 11/2 = 11/20 < 11/19
Vậy M < 11/19

a, \(\frac{1}{5.6}+\frac{1}{6.7}+...+\frac{1}{x\left(x+1\right)}=\frac{13}{90}\)
⇒ \(\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}+...+\frac{1}{x}-\frac{1}{x+1}=\frac{13}{90}\)
⇒ \(\frac{1}{5}-\frac{1}{x+1}=\frac{13}{90}\)
⇒ \(\frac{1}{x+1}=\frac{1}{5}-\frac{13}{90}\)
⇒ \(\frac{1}{x+1}=\frac{18}{90}-\frac{13}{90}\)
⇒ \(\frac{1}{x+1}=\frac{1}{18}\)
⇒ x + 1 = 18
⇒ x = 17
Vậy x = 17
b, \(\frac{1}{1.4}+\frac{1}{4.7}+\frac{1}{7.10}+...+\frac{1}{x\left(x+3\right)}=\frac{49}{148}\)
⇒ \(\frac{3}{1.4}+\frac{3}{4.7}+\frac{3}{7.10}+...+\frac{3}{x\left(x+3\right)}=\frac{49.3}{148}\)
⇒ \(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{10}+...+\frac{1}{x}-\frac{1}{x+3}=\frac{147}{148}\)
⇒ \(1-\frac{1}{x+3}=\frac{147}{148}\)
⇒ \(\frac{1}{x+3}=1-\frac{147}{148}\)
⇒ \(\frac{1}{x+3}=\frac{1}{148}\)
⇒ x + 3 = 148
⇒ x = 145
Vậy x = 145

Xét \(\frac{1}{\sqrt{13}}>\frac{1}{\sqrt{14}}\Rightarrow\frac{1}{\sqrt{13}}-1< \frac{1}{\sqrt{14}}+1\)
Mà \(\sqrt{225}< \sqrt{289}\)
\(\Rightarrow\sqrt{225}-\left(\frac{1}{\sqrt{13}}-1\right)< \sqrt{289}-\left(\frac{1}{\sqrt{14}}+1\right)\)
Vậy....................

\(A=\left(\frac{1}{2}-1\right)\left(\frac{1}{3}-1\right)\left(\frac{1}{4}-1\right)...\left(\frac{1}{10}-1\right)\)
\(\Rightarrow A=\frac{-1}{2}.\frac{-2}{3}.\frac{-3}{4}...\frac{-9}{10}\)
\(\Rightarrow A=\frac{-1}{10}\)
Dễ thấy \(\frac{1}{10}< \frac{1}{9}\Rightarrow\frac{-1}{10}>\frac{-1}{9}\)
\(A=\frac{-1}{2}.\frac{-2}{3}.\frac{-3}{4}.....\frac{-9}{10}\)
\(A=\frac{-1}{10}\)
\(\frac{-1}{10}>\frac{-1}{9}\Rightarrow A>\frac{-1}{9}\)
đ/s:..
uk cảm ơn bạn